Historical Study of ‘JĀTAKAS’: Special Reference to Buddhist Literature: Uncovering Untold Stories: Exploring Jātakas as a Record of Popular Tradition (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study is an attempt to understand oral traditions are rooted in assumptions about human actions and the nature of society even if the holders are unaware of their own beliefs. Using Jātakas as a text of popular tradition and as a historical source in the form of Oral tradition as a research method definitely helps in documenting previously undocumented information about rituals, customs, social organizations, myths, legends, indigenous science and knowledge, migration and origin. It also attempts to focus on the representation of the norms and values of superior culture as well as the inferior culture tradition of the common people who were earlier ignored by the texts of High culture. It also provides a multiple meanings of Reaffirmation, Subversion and ambiguity simultaneously. Hence, the structure of the Jātakas makes it possible to deal with every person and class of society that was not considered important for High culture society and tradition. This supplements the information already in the records, fills the gaps in the ethnographic data and brings out new and previously unknown facts about the society at the time of the Buddha.